Evaluating the Elements of Vitality in Jahānshahr Walkway, Karaj City, Iran - Mina Heydari Tamrabadi; Habibollah Fasihi; Tajaddin Karami (برنامه ریزی فضایی)
Abstract:The mental and social well-being of urban residents is greatly influenced by their exposure to vibrant and engaging physical environments and face-to-face interactions. The development of walkways is considered a crucial step toward achieving these goals. This research focused on evaluating the vitality indicators of Jahānshahr Walkway in Karaj City. The research methodology was descriptive-analytical, utilizing observational data collected through a checklist, as well as survey data obtained from a questionnaire. The sample population consisted of 270 randomly selected walkway users. Data analysis was conducted using EXCEL software, employing an innovative model. The findings revealed that the assessed walkway received a score of 4.666 (on a scale of 0-5), indicating a good level of vitality. However, Jahānshahr Walkway was lacking in certain social indicators, such as incorporation of cultural symbols, organization of festivals and rituals to attract people to the space, and presence of elements that appealed to children. On the other hand, its strengths lay in indicators, such as availability of recreational and leisure activities, diversity of leisure time options, and vibrancy of the walkway's surroundings, which were predominantly linked to the economic dimension. To enhance the vitality of the space, it is recommended to focus on preserving and expanding green areas catering to the needs of children, developing cultural identity and symbols, improving sanitation facilities, and ensuring convenient access to banks and services.Keywords: Vitality, Walkway, Public Space, Karaj City. Introduction:Vitality is recognized as a crucial attribute of sustainable cities as highlighted by the new urban agenda and the 11th sustainable development goal put forth by the United Nations. Within urban landscapes, public spaces, including passages, streets, and walkways, contribute to varying levels of vitality based on their unique characteristics. According to Jacobs, walkways are particularly vital components of urban public spaces. Construction of walkways in cities offers a practical and scientific solution to revive social life in city centers as they enhance the urban image, preserve historical areas and buildings, and restore a sense of identity to cities. Montgomery emphasizes vitality as one of the key quality factors in urban public spaces, particularly in the context of walkways. Furthermore, Mumford acknowledges the importance of pedestrian presence and the creation of pedestrian-oriented spaces as a means to reclaim the rights of urban residents that have been compromised with the introduction of motorized vehicles into urban environments. Understanding the true impact of urban environments on vitality is pivotal in designing vibrant and livable cities, ultimately enhancing the overall quality of life. This research aimed to evaluate the vitality components of Jahānshahr Walkway, a major thoroughfare that played a significant social, economic, and cultural role in the bustling and lively part of Karaj City, Iran. Materials & Methods:The study focused on Jahānshahr Walkway located in the northeastern region of Karaj, Iran. A total of 42 indicators were selected to assess the vitality of this walkway. Data collection was conducted through direct observation using a checklist, as well as a questionnaire administered to space users. A sample of 270 individuals randomly selected from the walkway users responded to the questionnaire. Data analysis was performed using EXCEL software, which involved calculating the average values for each questionnaire item, as well as the checklist data. These averages were utilized to evaluate the vitality of the space. Research Findings:Several indicators demonstrated scores higher than the mode and mean (3), indicating a favorable level of vitality. These indicators included "creating peace, comfort, and pleasure", "diversity of leisure time use", "existence of suitable economic activities for recreation and leisure time", "neatness and cleanliness", "vibrancy of the edges", "improving the pedestrian experience through effective architectural and landscape design", "flowering and green spaces", "appropriate lighting", "illumination of landmark buildings", "absence of landscape pollution", "facade design and visual aesthetics", "presence of passages connecting to surrounding spaces", "sufficient capacity for group gatherings", and "proper flooring". The average score for these indicators was 4.67. On the other hand, the lowest scores were observed in the indicators of "viewing cultural symbols and holding festivals and rituals that attract people to space" and "presence of attractive elements for children". When categorizing the indicators into the three sets of economic, physical-environmental, and socio-cultural indicators, the results indicated that the average scores for each set were 4.233, 4.227, and 3.310, respectively. This suggested that the economic, physical-environmental, and socio-cultural indicators contributed to higher levels of vitality in their respective sets.Discussion of Results & Conclusion:Based on the research findings, it could be inferred that certain parameters contributed to the attractiveness and vitality of the space. These included factors, such as incorporation of a diverse range of modern and traditional architectural plans, varied floor designs, alignment with the natural surroundings, a sufficient number of furniture installations, and presence of ample green spaces. However, there were also factors that had negatively impacted the vitality of the space, warranting consideration in future management and planning efforts for Karaj City. One of the notable shortcomings was the lack of attention to children's needs in the design and amenities provided along the walkway. Additionally, the symbols and elements representing identity and culture were relatively weak and access to banking services was challenging. The wide canals running alongside the walkway had also resulted in the accumulation of garbage, leading to suboptimal cleanliness levels. Furthermore, there was a lack of sanitary facilities, such as toilets and clean drinking water. In conclusion, while Jahānshahr Walkway demonstrated areas of vitality and attractiveness, there could be clear opportunities for improvement. Future management and planning initiatives should prioritize addressing the needs of children, enhancing cultural identity, improving access to banking services, ensuring proper waste management, and implementing adequate sanitation facilities, including toilets and clean drinking water provisions.